Bilateral optic perineuritis idiophatic: presentation of a clinical case: Perineuritis óptica bilateral idiopática: presentación de caso clínico - Prado-Molina, Diego Gerardo (2024)
Introduction: Optic perineuritis (PNO) is a rare inflammatory disorder that affects the optic nerve sheath, the cause of which may be idiopathic, infectious and/or autoimmune. The age of presentation is between 40 and 60 years, more frequently in women and with unilateral involvement, with bilateral presentation being exceptional. Case presentation: 82-year-old patient referred by an outpatient ophthalmology clinic to a hospital institution in the city of Medellín, Colombia, with a diagnostic impression of ischemic optic neuropathy due to clinical symptoms for 12 days with binocular horizontal diplopia, left frontotemporal headache of mild intensity and alterations in bilateral visual acuity. During her stay, she required help for diagnosis such as contrast-enhanced nuclear magnetic resonance imaging of the brain and orbit, which showed classic signs of bilateral optic perineuritis of an etiology to be clarified. Complementary serological and cerebrospinal fluid studies were performed that ruled out secondary causes, demonstrating a condition compatible with bilateral optic perineuritis of idiopathic origin. Discussion: PNO is a rare entity whose real prevalence is not clear worldwide. The most common clinical presentation is unilateral, of idiopathic origin, in patients between 40 and 60 years of age, with classic clinical signs and symptoms; Below, an exceptional case is presented that presented an atypical clinical picture with difficult diagnosis. Conclusions: This pathology is rare with a variable clinical behavior, which can present with binocular involvement as an uncommon presentation, being the most common cause of idiopathic origin. Keywords: Optical perineuritis, Idiopathic, Resonancia magnética nuclear, Visual Acuity, Optic Nerve, Orbit, Ophthalmology.